2017
DOI: 10.1016/j.semcdb.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Egg serpins: The chicken and/or the egg dilemma

Abstract: Twenty-seven serpins belonging to clade A, B, C, D, E, F, G, H and I serpins are currently referenced in chicken genome databases. Phylogenetic analysis of chicken serpins revealed that ovalbumin (Serpinb14) and its paralogs ovalbumin-related protein Y (Serpinb14b) and ovalbumin-related protein X (Serpinb14c) are found in bird species. These clade B serpins are specifically expressed in reproductive tissues and exported in the egg where they constitute major protein components. These data suggest that these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…However, our finding does not constitute a single observation, since the presence of such immunityassociated domains in shell proteins has already been noticed in different metazoan calcium carbonate biominerals: the shells of abalones [19,50], pearl oysters [2, 51,52], the giant limpet [29] and chicken egg shells [46]. It has been proposed that these molecules are involved either in immunological defence mechanism, or in the regulation of the matrix maturation, by controlling cleavage processes of other matrix proteins [53,54].…”
Section: Immunity-related Proteinsmentioning
confidence: 70%
“…However, our finding does not constitute a single observation, since the presence of such immunityassociated domains in shell proteins has already been noticed in different metazoan calcium carbonate biominerals: the shells of abalones [19,50], pearl oysters [2, 51,52], the giant limpet [29] and chicken egg shells [46]. It has been proposed that these molecules are involved either in immunological defence mechanism, or in the regulation of the matrix maturation, by controlling cleavage processes of other matrix proteins [53,54].…”
Section: Immunity-related Proteinsmentioning
confidence: 70%
“…Moreover, ACC was observed using cryo-electron microscopy inside the vesicles of the sea urchin cells involved in spicule mineralization (51,52). In this context, we paid particular attention to lysozyme (LYZ) and ovalbumin (OVA) that were identified in our proteomic study (Table 2 and 3), and were previously reported in chicken eggshell (62,67,69-71,73,89) and shown to modify calcite crystal morphology in vitro (90,91). The role of lysozyme in the stabilization of ACC has been explored but remains controversial.…”
Section: Discussionmentioning
confidence: 92%
“…OVA, OVALX and OVALY belonging to the serpin family, and have been previously identified in the eggshell matrix (63,90). Their role in calcium carbonate formation and ACC stabilization has been investigated (90,(96)(97)(98)(99). Calcium binds to ovalbumin and this accumulation creates a nucleation center for mineral formation (99).…”
Section: Discussionmentioning
confidence: 99%
“…However, these amino acid substitutions deserve more attention as embryo development and the synthesis of many egg components are sensitive to alterations in OVAL architecture . Keeping in mind the wide availability of these proteins in all the eggs compartments (Dombre et al 2017), the altered structure, biological activity, stability, or binding characteristics of ovalbumin proteins family seem to disrupt several biological pathways undertaken by chicks' embryos to take their schedules tasks of development and proper formation. It can be stated that the following nsSNPs H365P, I167T, V209G, L231P, F307C, and S317P should be absent in ovalbumin family in any chicken populations desired to be raised for higher egg production purposes.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to OVALX, it has been shown to exhibit antimicrobial activities against pathogens via its positively charged heparinbinding domain exposed at its surface (Rehault-Godbert et al 2013). These activities suggest considerable participation for OVALX in egg innate defense mechanisms (Dombre et al 2017;DaSilva et al 2019). Meanwhile, the role of OVALY has not been explored yet but because its physiological function is not known.…”
Section: Introductionmentioning
confidence: 99%